Best business practices and performance in ceramics industry in Thailand - Seedee, Rattana; Sulaiman, Mohamed; Ismail, Ishak (2009)
Many businesses have applied best practice for improving performance, but with mixed success. In addition, the results of past studies on the relationship between best business practices and performance are inconclusive. The aim of this study was to examine the extent to which ceramics industry has adopted the best business practices and whether these practices contribute to performance. Data were collected from 141 ceramics firms in Thailand. The results show that most of the ceramics firms adopted best business practices with a high degree of acceptance. The best practices of leadership, customer and market focus, process management, and product innovation proved to be significant and positively related to performance. The paper also discusses the implications and limitations of the study.